2007
DOI: 10.1007/s12017-007-0002-7
|View full text |Cite
|
Sign up to set email alerts
|

Brain tumor formation in tuberous sclerosis depends on erk activation

Abstract: Tuberous sclerosis (TS) is an autosomal dominant disease associated with the formation of usually benign tumors or hamartomas. The disease is connected with upregulation of mammalian target of rapamycin, central regulator of protein translation, which is usually regarded to be activated by Akt kinase. Here, we show for the first time that in all four brain lesions and one angiomyolipoma from TS patients both extracellular signal-regulated kinase (Erk) and p90 ribosomal S6 kinase 1 activation as well as Erk-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…our results are in agreement with Ess and colleagues who found GFaP positive staining in 50% (4/8) of the SEGas they analyzed (15). The results of their work illustrated the inconsistent presence of both glial and neuronal developmental markers in all their tumors and suggested SEGas may develop from postnatally active neuroglial progenitor cells activation is present in all SEGas and may also play a crucial role in tumor formation in tuberous sclerosis patients (19). our data support the observations of other groups, which have shown that LoH is uniquely sporadic in SEGas when compared to other tumors in TSC patients (3)(4)(5).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…our results are in agreement with Ess and colleagues who found GFaP positive staining in 50% (4/8) of the SEGas they analyzed (15). The results of their work illustrated the inconsistent presence of both glial and neuronal developmental markers in all their tumors and suggested SEGas may develop from postnatally active neuroglial progenitor cells activation is present in all SEGas and may also play a crucial role in tumor formation in tuberous sclerosis patients (19). our data support the observations of other groups, which have shown that LoH is uniquely sporadic in SEGas when compared to other tumors in TSC patients (3)(4)(5).…”
Section: Discussionsupporting
confidence: 92%
“…one possible explanation for presence of weakly positive immunostaining includes inactivation of the TSC heterodimer by tuberin phosphorylation by akt (18) or Erk (19) in cases without TSC gene mutations. Both akt and Erk kinases are located upstream of the TSC complex and are known to phosphorylate tuberin (TSC-2), which is thought to inhibit the GTPase enhancing activity resulting in mTor activation (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…In our earlier study [6] we observed both Akt and Erk hyperactivation in SEGA specimens. We also found that the Erk pathway plays a more important role in tumor formation in TS than Akt, as Erk hyperactivation without Akt was sufficient for tumor progression.…”
Section: Conclusion and Discussionmentioning
confidence: 61%
“…First of all, we focused on mTOR kinase and its activators. It is already known that both Akt and Erk pathways can be upregulated in SEGAs [6,7]. However, we do not know any previous study on mTOR, Akt or Erk pathways on SEN specimens.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation